The Role of the Immune System in Triplet Repeat Expansion Diseases - Marta Olejniczak; Martyna O. Urbanek; Wlodzimierz J. Krzyzosiak (Hindawi Limited, 2015)
Trinucleotide repeat expansion disorders (TREDs) are a group of dominantly inherited neurological diseases caused by the expansion of unstable repeats in specific regions of the associated genes. Expansion of CAG repeat tracts in translated regions of the respective genes results in polyglutamine- (polyQ-) rich proteins that form intracellular aggregates that affect numerous cellular activities. Recent evidence suggests the involvement of an RNA toxicity component in polyQ expansion disorders, thus increasing the complexity of the pathogenic processes. Neurodegeneration, accompanied by reactive gliosis and astrocytosis is the common feature of most TREDs, which may suggest involvement of inflammation in pathogenesis. Indeed, a number of immune response markers have been observed in the blood and CNS of patients and mouse models, and the activation of these markers was even observed in the premanifest stage of the disease. Although inflammation is not an initiating factor of TREDs, growing evidence indicates that inflammatory responses involving astrocytes, microglia, and the peripheral immune system may contribute to disease progression. Herein, we review the involvement of the immune system in the pathogenesis of triplet repeat expansion diseases, with particular emphasis on polyglutamine disorders. We also present various therapeutic approaches targeting the dysregulated inflammation pathways in these diseases.